The effect of daily meteorological parameters on the number of emergency service admissions by young and elderly patients - Yilmaz, Mustafa; Atescelik, Metin (Bayrakol Medical Publisher, 2023)
Aim: The aim of this study was to investigate the effect of daily meteorological parameters on the number of emergency department admissions of older adults.Material and Methods: This research was designed as a retrospective study. A list of all patients admitted to the emergency room between December 31, 2011 and January 01, 2021 was retrieved from the hospital records. Daily admissions to the emergency department and daily meteorological parameters were compared.Results: Linear regression analysis revealed a significant correlation between the number of female patients aged 18-65 years admitted to the emergency service and the mean daily temperature (p < 0.001) and mean daily relative humidity (p = 0.029). According to the results of linear regression analysis, a significant correlation was found between the number of male and female patients aged >= 65 years admitted to the emergency service and the mean daily temperature.Discussion: In particular, emergency service admissions of men and women aged >= 65 years show a positive correlation with the increase in temperature.
Keywords: Elderly; Temperature; Humidity; Atmospheric Pressure; Meteorological Parameters